Reproductive Outcomes after Diagnostic Laparoscopy in Primary Infertility - Firdous, Rakhshanda; Sultan, Shahida; Ahmad, Maqsood (Indus Journal of Bioscience Research, 2025)
Background: Primary infertility is an important issue in the area of reproductive health, causing physical, emotional, and social suffering to couples. Accurate diagnosis of pelvic pathology is important in improving fertility success. Diagnostic laparoscopy allows the inspection of pelvic structures and the potential correction of associated pathologies, which might improve the chances of both conception and maintaining pregnancy. Objective: To determine reproductive outcomes after diagnostic laparoscopy in women with primary infertility. Study Design: Cross sectional study. Duration and Place of Study: This study was conducted from September 2023 to December 2024 in the Department of Obstetrics and Gynaecology Lady Reading Hospital Peshawar. Methodology: A total of 115 women aged 25 to 40 years with primary infertility were included using consecutive sampling. Diagnostic laparoscopy was performed under standard operative conditions. Pelvic findings such as endometriosis, adhesions and ovarian pathology were identified and treated where required. Patients were followed for one year. Reproductive outcomes including positive pregnancy test, live birth and regular menstrual cycle were recorded. Chi square test was applied for stratification and a p value of ≤0.05 was considered significant. Results: The mean age of patients was 32.78 ± 4.50 years and mean duration of infertility was 5.12 ± 2.93 years. Positive pregnancy test was observed in 50.40% patients, live birth in 30.40%, and regular menstrual cycle in 85.20%. Conclusion: Diagnostic laparoscopy is an effective procedure for improving reproductive outcomes in women with primary infertility.